2023
DOI: 10.1038/s41598-023-43282-9
|View full text |Cite
|
Sign up to set email alerts
|

The oxidoreductase activity of Rnf balances redox cofactors during fermentation of glucose to propionate in Prevotella

Bo Zhang,
Christopher Lingga,
Hannah De Groot
et al.

Abstract: Propionate is a microbial metabolite formed in the gastrointestinal tract, and it affects host physiology as a source of energy and signaling molecule. Despite the importance of propionate, the biochemical pathways responsible for its formation are not clear in all microbes. For the succinate pathway used during fermentation, a key enzyme appears to be missing—one that oxidizes ferredoxin and reduces NAD. Here we show that Rnf [ferredoxin—NAD+ oxidoreductase (Na+-transporting)] is this key enzyme in two abunda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Since increased laboratory safety measures increases costs for biotechnological processes, we solely focused on species that belong to risk group 1 according to the German technical rule for biological agencies 466 (TRBA). Unfortunately, a well-studied propionate producer, Xylanibacter ruminicola [ 29 ] (formerly Prevotella ruminicola [ 30 ]) belongs to risk group 2. The species were selected either because they utilized a wide spectrum of polymeric substrates, for example B. cellulosilyticus , which had been described to degrade crystalline cellulose [ 31 ], or because comparably high propionate concentrations were reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since increased laboratory safety measures increases costs for biotechnological processes, we solely focused on species that belong to risk group 1 according to the German technical rule for biological agencies 466 (TRBA). Unfortunately, a well-studied propionate producer, Xylanibacter ruminicola [ 29 ] (formerly Prevotella ruminicola [ 30 ]) belongs to risk group 2. The species were selected either because they utilized a wide spectrum of polymeric substrates, for example B. cellulosilyticus , which had been described to degrade crystalline cellulose [ 31 ], or because comparably high propionate concentrations were reported.…”
Section: Resultsmentioning
confidence: 99%
“…Genes for the energy metabolisms identified were an Na + -gradient generating NADH-quinone reductase (Nqr), the Rnf complex and the cytochrome bd ubiquinol oxidase, which have been described previously for Bacteroidia [ 22 , 29 , 42 ]. In addition, B. graminisolvens harbored the genes for the NADH-quinone oxidoreductase without the subunits E, F and G, similar to the headless variant of this enzyme, that has been described before in Bacteroidia [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…5A ), three unrecognized enzymes have been found in two studies (Schleicher et al 2021 , Zhang et al 2023 ). The first study (Zhang et al 2023 ) found that Rnf is present, and as in P. ruminis , this enzyme transfers electrons away from reduced ferredoxin. This is important because a second enzyme was found that forms reduced ferredoxin.…”
Section: Diversity Of Fermentation Extends To the Biochemical Levelmentioning
confidence: 92%